Nest architecture in polydomous grass-cutting ants (Acromyrmex balzani) - Caldato, Nádia [UNESP]; da Silva Camargo, Roberto [UNESP]; Forti, Luiz Carlos [UNESP]; de Andrade, Ana Paula Protti [UNESP]; Lopes, Juliane Floriano Santos (Taylor & Francis, 2016)
ABSTRACT: Acromyrmex balzani is a grass-cutting ant species frequently found in Cerrado areas. However, little is known about the architecture of the polydomous nests of this ant. Fifteen A. balzani nests located in a cerrado region in Botucatu, São Paulo, Brazil, were studied. The polydomous nests were studied in three ways. First, we investigated the architecture in nests moulded with cement and without moulding. Second, we performed an aggressiveness test among workers in different subnests and nests. Third, we excavated the nest and collected the colony to measure the population, verifying the existence or not of a queen in all nests. A cement mould was made of seven nests to permit better visualization of internal structures such as chambers and tunnels. Eight nests were excavated without moulding and white neutral talc was used to highlight the parts of the nests. After excavation, the depth and dimensions (length, width and height) of the chambers were measured. The results showed that the nests had a single entrance hole whose structure consisted of straw and other plant residues in winter. Mounds of loose soil, if present, were found 6–48 cm from the hole. The number of chambers containing fungus ranged from one to five, with the first being found a few centimetres beneath the ground surface (4 cm) and the last up to a maximum depth of 160 cm. The length of the tunnels ranged from 12 to 28 cm. These tunnels were built in a vertical or inclined position, leading to the chambers. No waste chambers were found, with the waste being deposited externally. Additionally, the polydomous nests contained one to eight subnests. In the aggressiveness test, when concolonial workers were confronted, no aggressiveness was observed. In contrast, when allocolonial workers were confronted, there was a high incidence of aggression among them. Excavation of polydomous nests showed only one queen for each polydomous nest, i.e. subnests with a single queen. Our study contributes to a better understanding of the so far unknown nest architecture of the polydomous grass-cutting ant A. balzani.
Keywords: Grass-cutting ants; nest; social insects